Phages against killer superbugs: An enticing strategy against antibiotics-resistant pathogens - Baral, Bikash (Frontiers in Pharmacology, 2023)
The emerging resistivity of antibiotic resistance superbugs desires the need to resolve the global problem of antibiotic resistance. Among several other methods currently being adopted, one possible solution may be the development of supplemental therapies for antibiotics. The use of the normal and advanced bactericidal properties of bacteriophages (bacteriophage therapy) may be one of the viable infection control options. It is evident, however, that the safe and regulated application of phage treatment will need extensive knowledge of the characteristics and behavior of certain phage–bacterium systems. This mini-review offers an overview of the potential for phage therapy as well as the constraints and obstacles it faces in becoming a commonly accepted infection management strategy.